Pengaruh Indeks Pembangunan Manusia dan Tingkat Pengangguran Terbuka Terhadap Kemiskinan di Kabupaten Simalungun - Sri Maya Ningsih; Indah Pertiwi Siregar; Humitcha Manalu; Safuridar (Akuntansi, 2023)
The purpose of this study is to ascertain how Simalungun poverty rate fluctuates by the Human Development Index (IPM) and Open Unemployment Rate (TPT). Secondary data from the Simalungun Central Bureau of Statistics (BPS) has been utilized in this study. For 23 districts and cities in Simalungun, a panel random effect model was utilized from 2023. The findings indicated that HDI and TPT decisively and adversely impacted Simalungun poverty levels. The government must thus confirm the riil data on the unemployment rate by address and encourage more unemployed others to develop their skills and knowledge by offering mentoring, funding, and more help for MSMEs, as well as by recruiting in new industries. The administration is anticipated to keep raising the bar regarding human development.